2003
DOI: 10.1055/s-2003-37718
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development of Antitumor Agents from Chinese Herbal Medicines; Part I. Low Molecular Compounds

Abstract: A series of low molecular compounds from Chinese herbal medicines which have proved to be, in some cases, highly effective especially in tumor therapy, is listed here (part II will deal with high molecular compounds, to be published in the next issue). In contrast to synthetic agents used in cancer chemotherapy, these natural compounds have relatively low toxicities. Many of the clinical studies referred to in this paper have been carried out on Asians. Because genetic factors influence enzyme levels, sometime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 63 publications
0
41
0
1
Order By: Relevance
“…Natural products have been potential sources of novel anticancer drugs over the last few decades (8,9). Many synthetic compounds have been based on key structural features of the bioactive compounds isolated from herbal plants.…”
mentioning
confidence: 99%
“…Natural products have been potential sources of novel anticancer drugs over the last few decades (8,9). Many synthetic compounds have been based on key structural features of the bioactive compounds isolated from herbal plants.…”
mentioning
confidence: 99%
“…Comparatively, CnB is easy to express and to purify (42), and the cost of CnB is lower than that of other protein drugs. Unlike some antitumor agents, that have to be extracted from Chinese herbs (43,44), CnB does not have any disadvantages for the environment.…”
Section: Discussionmentioning
confidence: 99%
“…[68][69][70][71][72][73] The poor solubility of this compound encouraged researchers to design analogs with improved physico-chemical characteristics. Indeed, it was found that appending a basic heterocycle side chain onto the lactam nitrogen resulted in significantly better solubility than Meisoindigo while retaining good activity against leukemia K562.…”
Section: The Biological Activity Of Isoindigosmentioning
confidence: 99%